A Cyclic Shift Chirp Modulation Scheme for Analog Message with Simplified PPM Demodulation - Kaew-In, Chanapat; Wardkein, Paramote; Chatchaiphat, Nisukan; Chodkaveekityada, Peeramed (My University, 2026)
In this work, a cyclic shift chirp modulation scheme with an analog message signal is presented. The demodulation process is carried out by converting the cyclic shift chirp into pulse position modulation (PPM), followed by three demodulation approaches: (i) direct LPF filtering of the PPM pulses, (ii) inversion of the PPM pulses prior to LPF filtering, and (iii) integration driven by the PPM pulses. The recovered signal in these cases corresponds to the differentiated form of the original message signal. However, when the message signal is preintegrated before PPM modulation, the subsequent demodulation via integration directly yields the original message signal, eliminating the need for an additional integration stage at the receiver. This results in a simplified and less complex receiver compared to conventional PPM schemes without input pre-integration. Analytical and experimental results are in close agreement, validating the effectiveness of the proposed method.
Keywords: analog modulation and demodulation; cyclic shift chirp; pulse position modulation